FAKTOR – FAKTOR YANG MEMPENGARUHI PRAKTIK INCOME SMOOTHING - Natasha Hadi; Widyasari Widyasari (Jurnal Paradigma Akuntansi, 2023)
The purpose of this research is to obtain empirical evidence about the effect of ptofitability, financial leverage, auditor reputation, and firm size as moderating variable on income smoothing practices in manufacturing companies listed on Indonesia Stock Exchange in 2017-2019. The method used in this research is purposive sampling and obtain 151 final sample. This research used SPSS Version 25 Program to process the data. The technique used in this research is logistic regression analysis. The result of this research indicate that profitability and financial leverage have a positive effect, while auditor reputation have a negative effect on income smoothing, and firm size can weaken the effect of profitability, financial leverage, and auditor reputation on income smoothing.